2018
DOI: 10.2147/ott.s173001
|View full text |Cite
|
Sign up to set email alerts
|

Siva-1 emerges as a tissue-specific oncogene beyond its classic role of a proapoptotic gene

Abstract: Siva-1 is a typical apoptotic protein commonly activated by the p53 tumor suppressor protein and should therefore participate in a barrier against the development of cancer. It has proapoptotic activities in various cell systems. Recent findings suggest that Siva-1 possesses several other apoptosis-independent functions and interacts with many other proteins not directly involved in apoptosis. It harbors the ARF E3 ubiquitin protein ligase activity, a property that is clearly prooncogenic and leads to p53 degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…lV, lentivirus; Mdr1, multidrug resistance 1; MrP1, multidrug resistance protein 1; nc, negative control; Vcr, vincristine. The Siva-1 protein serves a crucial role in certain extrinsic and intrinsic apoptosis signaling pathways (16). However, Siva-1 has been demonstrated to serve contradictory roles in previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…lV, lentivirus; Mdr1, multidrug resistance 1; MrP1, multidrug resistance protein 1; nc, negative control; Vcr, vincristine. The Siva-1 protein serves a crucial role in certain extrinsic and intrinsic apoptosis signaling pathways (16). However, Siva-1 has been demonstrated to serve contradictory roles in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…gene is located on chromosome 14 (14), a region which is often targeted for chromosomal translocation. Previous studies have demonstrated that Siva-1 arrests apoptosis and facilitates cancer development in osteosarcoma, hepatocellular carcinoma and non-small cell lung cancer (15)(16)(17)(18). However, the molecular function of Siva-1 regulating multidrug resistant in gastric cancer currently remains uncertain as previous studies have presented confusing and ambiguous results (16), which has prompted further investigation into both its function and associated signaling pathway.…”
Section: Siva-1 Regulates Multidrug Resistance Of Gastric Cancer By Targeting Mdr1 and Mrp1 Via The Nf-κb Pathwaymentioning
confidence: 99%
“…TARBP2 and YBX-1 are central regulators of DICER/Ago2 mediated miRNAs processing in GBM (Frohn et al, 2012; Wu et al, 2015), consistent with the particular heightened role of epigenetic mechanisms, including those mediated by miRNAs and non-coding RNAs, play in GBM plasticity (Balci et al, 2016; Li et al, 2016; Peng et al, 2018; Zhang et al, 2015). SIVA1 is an E3 ubiquitin ligase that promotes degradation of the tumor suppressor and cell cycle checkpoint protein ARF, which in turn downregulates p53 (Vachtenheim et al, 2018; Van Nostrand et al, 2015; Wang et al, 2013). Loss of p53 and ARF are classical features of glioblastoma (Kim et al, 2012; Mao et al, 2012; Zheng et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Beyond its role in apoptosis, SIVA-1 also regulates other cellular processes, such as cellular migration ( Li et al, 2011 ; Ma et al, 2017 ), autophagy ( Van Nostrand et al, 2015 ), and proliferation ( Ma et al, 2017 ; Liu et al, 2020 ). In cancer studies SIVA-1 has been found to have a role as pro- or anti-malignant factor, depending on cellular context ( Vachtenheim et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%